Practice guideline update summary: Efficacy and tolerability of the new antiepileptic drugs I. (10th July 2018) - Kanner, Andres M.; Ashman, Eric; Gloss, David; Harden, Cynthia; Bourgeois, Blaise; Bautista, Jocelyn F.; Abou-Khalil, Bassel; Burakgazi-Dalkilic, Evren; Llanas Park, Esmeralda; Stern, John; Hirtz, Deborah; Nespeca, Mark; et al.
Abstract : Objective: To update the 2004 American Academy of Neurology (AAN) guideline for treating new-onset focal or generalized epilepsy with second- and third-generation antiepileptic drugs (AEDs). Methods: The 2004 AAN criteria were used to systematically review literature (January 2003–November 2015), classify pertinent studies according to the therapeutic rating scheme, and link recommendations to evidence strength. Results: Several second-generation AEDs are effective for new-onset focal epilepsy. Data are lacking on efficacy in new-onset generalized tonic-clonic seizures, juvenile myoclonic epilepsy, or juvenile absence epilepsy, and on efficacy of third-generation AEDs in new-onset epilepsy. Recommendations: Lamotrigine (LTG) should (Level B) and levetiracetam (LEV) and zonisamide (ZNS) may (Level C) be considered in decreasing seizure frequency in adults with new-onset focal epilepsy. LTG should (Level B) and gabapentin (GBP) may (Level C) be considered in decreasing seizure frequency in patients ≥60 years of age with new-onset focal epilepsy. Unless there are compelling adverse effect–related concerns, ethosuximide or valproic acid should be considered before LTG to decrease seizure frequency in treating absence seizures in childhood absence epilepsy (level B). No high-quality studies suggest clobazam, eslicarbazepine, ezogabine, felbamate, GBP, lacosamide, LEV, LTG, oxcarbazepine, perampanel, pregabalin, rufinamide, tiagabine, topiramate, vigabatrin, or ZNS is effective in treating new-onset epilepsy because no high-quality studies exist in adults of various ages. A recent Food and Drug Administration (FDA) strategy allows extrapolation of efficacy across populations; therefore, for focal epilepsy, eslicarbazepine and lacosamide (oral only for pediatric use) as add-on or monotherapy in persons ≥4 years old and perampanel as monotherapy received FDA approval.